Somatotype of School Going Girls at the Age of Menarche of a Peripheral District of Bangladesh - Begum, Mahfuza; Anwar, Selina; Habib, Md Ahsan; Roy, Happy; Begum, Munnuzan (Bangladesh Journal of Anatomy, 2019)
Context: Human populations consist of individuals who differ widely in body shapes and sizes. Somatotypes are morpho-phenotypic ranges along with continuation of variation, which possess constantly recognizable characteristics and are the functional end products of the whole genetic and the developmental complex. This study was conducted with the objective to find out the difference of somatotype of children at the age of menarche in the rural and the urban areas in a district of Bangladesh. Materials and Methods: Somatotypes of school going girls age ranging from 12 to 16 years were considered in a cross sectional descriptive type of study and was carried out at the department of Anatomy, Rangpur Medical College from July 2014 to June 2014. A total of 200, 100 rural and 100 urban students were included from the urban and the rural schools respectively. A pre-tested, structured, self-administered questionnaire was set for obtaining the socio-demographic data (age at menarche, number of sibling of the students and occupation and educational attainment of their parents, etc.). A series of measurements were obtained by direct measurements. Results: It was found that the urban students had a higher mean value for endomorphic and mesomorphic scores than rural students and the difference was statistically highly significant (p<0.000). On the other hand ectomorphic score was slightly higher in urban students than rural students but was not statistically significant (p>05). The endomorphic and mesomorphic scores of urban students were 4.99 ±0.73 & 2.21±1.3 and those of rural students were 4.45±0.40 & 1.48±1.0 respectively. Ectomorphic scores of urban and rural students were 2.87±1.5 & 2.82 ±0.85 respectively. The mean menarcheal age in case of urban students was 11.83±0.82 years and in case of rural students was 13.61±0.83 years. Conclusion: The findings indicated that urban girls were significantly more endomorphic and mesomorphic than rural girls. Bangladesh Journal of Anatomy January 2019, Vol. 17, No. 1, pp. 14-20